Pengaruh Kemiringan Sudut Hopper Input Pada Mesin Pencacah Sampah Organik Terhadap Kapasitas Produksi Mesin - Saparin Saparin; Eka Sari Wijianti; Budi Santoso Wibowo; Yudi Setiawan (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
There are two types of waste, organic and inorganic waste. Organic waste can be used as compost with great potential to be developed, the high amount of wasted organic waste is not reused, which causes the waste to accumulate and will eventually be burned. This research is about designing an organic waste chopping machine. The engine specifications include a 6.5 HP gasoline engine, pulley and belt transmission, and overall engine measurements of 1918 mm in length, 639 mm in width, and 1046 mm in height. The dimensions of the blade are 160 mm long, 60 mm wide and 10 mm thick.The blade's cutting angle has a 30 degree slope. The chopping blade shaft rotates between 1694 and 1741 rpm. This study adjusts the input hopper's slope angle at 50 degree, 60 degree, and 70 degree depending on the machine's production capacity and productivity. There are machines that can produce 180 kg per hour to 449 kg per hour.The highest capacity occurs at the variation of the 50 degree input hopper slope reaching 449.55 kg/hour. The lowest capacity at the variation of the slope angle of 70 degree is 183.16 kg/hour. Machine production efficiency ranges from 89% to 93%.